Prevalence of Atherosclerotic Disease in Microscopic Colitis Patients - Paul Hong; Karolina Krawczyk; Rehmat U. Awan; Raza Hasan; Poornima Oruganti; Xianzhong Ding; Michael Wesolowski; Ayokunle T. Abegunde (Gastro Hep Advances, 2023)
Background and Aims: The preponderance of microscopic colitis (MC) in females may be associated with postmenopausal increased risk of atherosclerosis. The aim of this study was to describe the prevalence of atherosclerotic diseases in adults with MC. Methods: Retrospective observational study of patients with a diagnosis of MC or incomplete MC at our institution from 2008 to 2018. We performed a chart review and extracted data on demographics, comorbidities, medications, diagnosis, imaging, and endoscopy. Data were analyzed descriptively. Logistic regression was used to estimate the unadjusted effects of different variables on MC. Results: Of 269 patients, 265 had a MC diagnosis; 236 (89.06%) had collagenous colitis or lymphocytic colitis; and 29 (10.94%) were diagnosed with incomplete MC. Majority were female (79.55%), ≥ 65 years (59.11%), and white (88.81%). Majority had the following risk factors for atherosclerosis, smoking (52.04%), hypertension (58.21%), and hyperlipidemia (59.5%). The prevalence of coronary artery disease (CAD), peripheral artery disease (PAD), and cerebrovascular disease (CVD) was 16.79% (12.32, 21.27), 8.58% (5.23–11.94), and 7.49% (4.33–10.65), respectively. There was no difference in the prevalence of CAD and CVD after adjusting for sex. Females with MC had reduced odds of PAD compared with males. Conclusion: The prevalence of CAD, PAD, and CVD was 16.79%, 8.58%, and 7.49%, respectively. Similar to the general population, smoking, hypertension, and hyperlipidemia are risk factors for atherosclerosis in MC.